Copper-Catalyzed Acetylation of Electron-Rich Phenols and Anilines - Zhang, Jieyu; Ke, Qiumin; Tian, Feitao; Jiang, Bei; Ji, Chang-An; Zhang, Lingling; Yu, Jian; Huang, Dayun; Yan, Guobing (Synlett, 2019)
An approach has been developed for the copper-catalyzed acetylation of phenols and anilines with potassium thioacetate as an acetylating reagent. Although only electron-rich phenols and anilines are compatible with this protocol, the reaction can provide moderate to high yields under mild conditions. Compared with other acetylating reagents, the current reagent has certain advantages, such as its low cost, easy availability, stability, insensitivity to water or air, and ease of storage.
Keywords: acetylation; phenols; anilines; copper catalysis; potassium thioacetate; butyl nitrite